A facilitated expert‐based approach to architecting "openable" complex systems. Issue 1 (19th January 2018) - Szajnfarber, Zoe; Vrolijk, Ademir
Abstract: Open innovation methods, which broadly include: prize competitions, grand challenges, and collaborative communities, are increasingly being applied to complex systems problems. While external solvers (i.e., the crowd) have historically contributed some important innovations, there appears to be a limit to the kind of systems where open innovation can be successful. We contend that open innovation activities can be more broadly effective if seekers (i.e., problem owners) formulated their system architectures with "openability" in mind. In this paper, we build on existing theory to categorize the kinds of problems that are most amenable to crowd contributions, based on the mechanisms of solving. We call these "openable" problems. We then develop and demonstrate an architecting process that uses a facilitated expert workshop to elicit "openable" subproblems within a given systems‐level problem. It treats the need for some openable subproblems as a constraint on the architecture. While not all systems should be designed with "openability" in mind, many organizations have faced political‐level pressure to better leverage the crowd. In that context, we provide guidance on how to do so effectively. We demonstrate the potential value of our approach through application to the NASA Asteroid Grand Challenge—a highly complex system. The paper concludes by reflecting on the implications of this exercise for open innovation and system decomposition in general.